MPR DALAM SISTEM KETATANEGARAAN INDONESIA (STUDI KOMPARATIF ANTARA SEBELUM DAN SESUDAH PERUBAHAN UUD 1945) - Santika, I Wayan Eka; Sujana, I Gede (Institut Hindu Dharma Negeri Denpasar, 2021)
The purpose of this research was to determine the People's Consultative Assembly in the Indonesian constitutional system. This research was a type of library research which is descriptive analytic through a qualitative approach that is based on comparative studies. The results of this research indicated that there are fundamental differences between the People's Consultative Assembly before and after the amendment to the 1945 Constitution. The differences included (1) the change in the position of the People's Consultative Assembly from the highest state institution to a state institution that is equal to other state institutions, (2) changes in the membership structure of the People's Consultative Assembly from those previously consisted of House of Representatives, Group Envoys and Regional Representatives, then became members of the House of Representatives and Regional Representative Board members, (3) the policy to appoint People's Consultative Assembly members was replaced by an election system, (4) the People's Consultative Assembly no longer stipulates the Broad Outlines of the Nation's Direction along with filling the position of President through participation the people directly in the election, (5) limitation of the People's Consultative Assembly's authority in amending the 1945 Constitution, (6) the inauguration of the President and / or Vice President in normal and abnormal conditions, (8) the authority of the People's Consultative Assembly to dismiss the President and / or Vice President must be through a forum previlegiatum.Keywords: People's Consultative Assembly, State Administration, Amendment to the 1945 Constitution.